Dyes from the Southern Lands: An Alternative or a Dream? - María Fernanda Cerdá (Solar, 2022)
DSSC technology based on natural dyes still constitutes a tempting alternative to explore. Besides the ease of extraction, most natural dyes fulfill the characteristics to be applied as sensitizers. The presented results summarize the exploration of the features of several southern dyes, mostly coming from the Antarctic region. The explored pigments showed good absorption capacity within the visible region of the light spectra, and their molecules possess functional moieties to coordinate with the TiO2 semiconductor, oxidation potential value near 1 V and reduction potential near −0.8 V, adequate thermal stability, and low fluorescence emission.